Designing Embedded Systems with Arduino A Fundamental Technology for Makers - Pan, Tianhong (Springer Singapore, 2018)
In this DIY guide, you will learn how to use Arduino - the open-source hardware board for makers, hobbyists, and inventors. You will learn how to develop your own projects, create prototypes, and produce professional-quality embedded systems. A simple step-by-step demonstration system accompanies you from vision to reality - and just like riding a bike, you'll get better at it, the more you do it. Featuring a wealth of detailed diagrams and more than 50 fully functional examples, this book will help you get the most out of this versatile tool and bring your electronic inventions to life.